Adição combinada de carboidrases e óleos essenciais em dietas de novilhos confinados ssp - Abreu, Jorge Augusto Dias da Costa (2017)
The objective of this work was to evaluate the associative effect of carbohydrase enzymes and essential oils on the performance, intake and digestibility of dry matter, ruminal temperature and carcass traits of finished bulls in feedlot receiving a high energy density diet. The experimental period had a duration of 70 days, being 07 days of adaptation and 63 days of data collection. Thirty 40 breeding Angus and ½ Nellore blood steers were used, with a mean age of 14 months and a mean weight of 436 kg. The experimental design was completely randomized, consisting of four treatments and five replications, in which each repetition was represented by a bay with two animals. The treatments consisted of the inclusion of the following additives: T1 - control; T2 - enzymatic complex, at the dose of 5 g animal day-1; T3 - mixture of essential oils, at the dose of 8 g animal day-1; and T4 - enzyme complex at the dose of 5 g animal day-1 plus essential oils mixture at the dose of 8 g animal day-1). The diets were constituted in constant ratio of 85% of whole corn grains and 15% of pelleted mineral vitamin protein core, in the dry basis. Among the evaluated parameters, those that presented a significant difference between the treatments were CMS in which T1 had 8.414kg d-1 on average, T2 8,018kg d-1, T3 7,628kg d-1 and T4 7,501kg d-1, consumption reduction from T1 to T4 with final weight gains and similar GMD. There was no effect for EA and CA; The apparent digestibility of T4 MS was higher than T1 (T1- 77.55%, T2- 79.95%, T3- 81.69% and T4- 83.24%); The parameters of carcass characteristics were not affected, nor was there interference of the treatments in the design and viscera weight; The ruminal temperature was affected by the treatment only in period 3 in which T4 was smaller than T1 the values found form T1- 40,46º, T2- 38,51º, T3- 37,64º and T4- 36,83º. According to the results, the association of carbohydrase enzymes and essential oils, in this dosage, in this experiment, showed a decrease in CMS without GMF and GMD alteration, increase of the digestibility of the diet and reduction of ruminal temperature in the third period evaluated in systems of cattle receiving high energy density diets.